Modeling of innovative technology of fruit and berry desserts - Polovyk, Volodymyr; Koretska, Iryna; Kuzmin, Oleg; Zinchenko, Tatiana (My University, 2020)
The aim of the work is to create a mathematical model for determining the balance of biologically active substances in prescription compositions of desserts made using blended semifinished vegetable raw materials. The task of the study is to determine the composition of the blended prescription mixture of a model pair of vegetable puree with the maximum content of biologically active substances. Results. The scientific novelty of the obtained results is that for the first time mathematical models of blended pairs were obtained and physicochemical and organoleptic parameters of innovative desserts were studied. Used modern research methods organoleptic, physicochemical; mathematical processing of experimental data was performed using computer technology. According to the results of organoleptic evaluation, the rating score of apple-dogwood dessert exceeded the control sample on apple puree (97.72 vs. 91.18б).Метою роботи є створення математичної моделі для визначення балансу біологічно активних речовин в рецептурних композиціях десертів виготовлених з максимальним вмістом біологічно-активних речовин використанням купажних напівфабрикатів рослинної сировини. є визначення складу купажної рецептурної суміші модельної пари рослинного пюре з Наукова новизна отриманих результатів полягає в тому, що було вперше отримано математичні моделі купажних пар та досліджено фізико-хімічні та органолептичні показники інноваційних десертів. Використовували сучасні методи дослідження органолептичні, фізико-хімічні; математичну обробку експериментальних даних проводили за допомогою комп’ютерних технологій. За результатами органолептичної оцінки рейтинговий бал десерту яблуко-кизил перевищив контрольний зразок на яблучному пюре (97,72 проти 91,18 балів2).
Keywords: restaurant products; blended semi; finished product; mathematical modeling; desserts; quality assessment; ресторанна продукція; купажований напівфабрикат; математичне моделювання; десерти; кафедра технології ресторанної і аюрведичної продукції; кафедра вищої математики імені проф. Можара В. І.